2002
DOI: 10.1024//1421-0185.61.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Commitment to pro- versus counter-attitudinal behavior and the dynamics of social representations

Abstract: This research uses the counter-attitudinal essay paradigm ( Janis & King, 1954 ) to test the effects of social actions on social representations. Thus, students wrote either a pro- or a counter-attitudinal essay on Higher Education. Three forms of counter-attitudinal essays were manipulated countering respectively a) students’ attitudes towards higher education; b) peripheral beliefs or c) central beliefs associated with this representation object. After writing the essay, students expressed their attitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 16 publications
0
13
0
1
Order By: Relevance
“…Table ) in order to determine their respective structural status (cf. Tafani & Souchet, ; as well as Tafani, Souchet, Codaccioni, & Mugny, ). These show that the negation of the cognitions “preserving natural resources” (83%; Fisher's exact test, p = .001), “preserving the future for the generations to come” (77%; Fisher's exact test, p = .001), and “preserving the environment” (69%; Fisher's exact test, p = .002) results in frequencies of refutation significantly superior to an equifrequency norm, which shows their central status in this population in the sense that their negation results in the fact that a large majority of the participants no longer consider the activity that is presented to them as an energy saving.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Table ) in order to determine their respective structural status (cf. Tafani & Souchet, ; as well as Tafani, Souchet, Codaccioni, & Mugny, ). These show that the negation of the cognitions “preserving natural resources” (83%; Fisher's exact test, p = .001), “preserving the future for the generations to come” (77%; Fisher's exact test, p = .001), and “preserving the environment” (69%; Fisher's exact test, p = .002) results in frequencies of refutation significantly superior to an equifrequency norm, which shows their central status in this population in the sense that their negation results in the fact that a large majority of the participants no longer consider the activity that is presented to them as an energy saving.…”
Section: Resultsmentioning
confidence: 95%
“…The relation between social representation and commitment (cf. Moscovici, ) was first considered in works on representational dynamics (Renard, Bonardi, Roussiau, & Girandola, ; Souchet & Tafani, ; Tafani & Souchet, , ). The relation between social representation and commitment was studied more recently from another perspective (Eyssartier, Joule, & Guimelli, ).…”
Section: Social Representations and Commitmentmentioning
confidence: 99%
“…Including social identification in the diagnosis of the structure of an SR would become an interesting factor since it would be involved in the convergence of the members of the group with regard to their way of thinking about the object and thus in the structuring of the representation. This aspect would be very important, for example, in research on the “ SR Structure Effect ” (Skandrani‐Marzouki et al, ) in the context of cognitive processes related to social influence (e.g., Mugny, Souchet, Codaccioni, & Quiamzade, ), attitude change (e.g., Tafani & Souchet, ), social comparison (Chokier & Rateau, ), behavioral commitment (e.g., Piermattéo et al, ; Souchet & Girandola, ; for a recent review, see Lo Monaco et al, in press) or in research linking the structure of social representations to emotions (e.g., Skandrani‐Marzouki et al, ). Thus, these investigations require prior identification of the structure of the SR. Future research may need to strengthen these essential theoretical links between the SR theory and identity approaches in order to provide information that will lead to methodological solutions.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, from the outset, “the arbitrary cutoff point” (Moliner, , p. 277) of 75% was proposed and is still used in many studies (Flament, ). Secondly, some studies (e.g., Roussiau & Bonardi, ; Tafani & Souchet, ) used a norm of equi‐frequency using the chi 2 ‐test. This method of data analysis considers elements as central when the proportion of refutations differs significantly from a random distribution.…”
Section: Methods For Studying the Structure And Organization Of Sociamentioning
confidence: 99%
“…Tafani (2001) observed that the attitudes towards beliefs expressed in central elements are more resistant to transformation caused by writing a counter-attitudinal essay than the attitudes related to peripheral elements. Likewise, Tafani and Souchet (2002) observed that the commitment to a behavior that challenges an attitude or peripheral belief can affect the evaluations of peripheral elements only. Structural changes only take place when a challenging behavior implies a central element of the social representation.…”
Section: Characteristics Of Central and Peripheral Elements Of Socialmentioning
confidence: 99%